Dissecting human ILC heterogeneity: more than just three subsets. Issue 3 (26th December 2017) - Simoni, Yannick; Newell, Evan W.
Summary: Innate lymphoid cells (ILCs) have been divided into three distinct groups based on functional capacities, cytokine profiles and transcription factor expression. Studies performed mainly in mice have demonstrated the importance of ILCs in chronic inflammation, infection, allergy and cancer. In this review, we discuss the heterogeneity of human ILC and focus primarily on the taxonomy of human ILC cell subsets and their phenotypical and functional diversity. We summarize recent findings concerning the diversity of ILCs between and within the major subsets [natural killer (NK), ILC1, intra‐epithelial ILC1 (ieILC1), ILC2, ILC3, lymphoid tissues inducer (LTi) and ILC progenitor (ILCP)], as well as the abundance of each in human tissues. We also discuss the similarities observed between groups of cells in term of receptors expressed and cytokines produced, and how these relate to the pleiotropic properties of each subset. Abstract : Dissecting human ILC heterogeneity: more than just three subsets. We summarize recent findings about the diversity of ILCs between and within the major subsets (NK, ILC1, ieILC1, ILC2, ILC3, LTi, ILCP), as well as the abundance of each in human tissues. We also discuss the similarities observed between groups of cells in term of receptors expressed and cytokines produced, and how these relate to the pleiotropic properties of each subset.